Assessment of disease progression in patients with RMT carcinoma - A retrospective analysis of the associated factor. - MURTHY, SINDHU PRIYA KUPPUSAMY SUNDARA; DR. MAHATHI. N; DR. SURESH (The journal of contemporary issues in business and government, 2020)
Retromolar trigone is a subsite of oral cavity. It is a triangular mucosal area between the ascending ramus of the mandible attached to the muscles of mastication. Only at advanced stages after it involves the mandible or masticatory muscle does it result in severe pain or trismus. Data samples required for study were taken from hospital records. All the collected data were cross verified and compiled together in an excel sheet. Compiled data were statistically analysed in SPSS software. In this study of 27 patients, before treatment about 50% (14) had symptoms of trismus, after treatment out of the 50% of patients with trismus, 35.71% had 2 finger breadth mouth opening (trismus) and the rest of the patients (64.29%) had 3 finger breadth mouth opening.